THE METHOD OF SHAYKH NAWAWI AL-BANTENI IN HADITH COMMENTARIES OF TANQIH AL-QAUL - Kirin, Arwansyah bin; Masruri, Muhammad (RIWAYAH, 2022)
Shaykh Nawawi al-Banteni is an Islamic scholar who produces various famous works in the archipelago, especially in Indonesia. Among his famous works is the book Tanqih al-Qaul is one of the interpretes or reviews from the book Lubab al-Hadith by Jalal al-Din al-Suyuti.This book became a reference in some Indonesian Boarding Schools. In addition, it is also used as a book study material in certain mosques. However, in-depth study of the method of hadith interpretes in the book is rarely observed by users of the book. Therefore, it is important to explain the method of hadith interpretes found in this book so that its status can be known as well as to measure the extent of its knowledge in the hadith. This study aims to explore the method of hadith interpretes conducted by Shaykh Nawawi al-Bantani in the book Tanqih al-Qaul. The purpose of this study is to determine and analyze the method of hadith interprete used by Shaykh Nawawi al-Banteni and reveal the extent of his knowledge and status as a scholar of hadith through the book Tanqih al-Qaul. The methodology of this study is qualitative through library methods and content analysis design of Tanqih al-Qaul book. This study found that in general the method used by Shaykh Nawawi al-Banteni in interpreting hadith is by using the method of Ijmali. In its application, he uses textual interpretation techniques through the method of interpreting hadith according to the original material or text of hadith, and intertextual through the method of reciting hadith with hadith. This study found that Shaykh Nawawi al-Banteni had good ability and knowledge in hadith. Apart from that, it can also provide an understanding to the community about the method of hadith interprete performed by Shaykh Nawawi al-Banteni in his book Tanqih al-Qaul.[Manhaj Shaykh Nawawi al-Banteni dalam Mensyarahkan Hadith-Hadith Kitab Tanqih Al-Qaul. Shaykh Nawawi al-Banteni merupakan seorang cendekiawan Islam yang menghasilkan pelbagai karya yang masyhur di Nusantara khususnya Indonesia. Di antara karya beliau yang terkenal itu adalah kitab Tanqih al-Qaul merupakan salah satu syarah atau ulasan dari kitab Tanqih al-Qaul syarahan dari kitab Lubab al-Hadith karangan Jalal al-Din al-Suyuti. Kitab   ini  menjadi   referensi di beberapa pondok pesantren Indonesia, selain itu dia juga dijadikan sebagai bahan kajian kitab di masjid-masjid tertentu. Namun,  kajian mendalam tentang manhaj syarahan hadith dalam kitab tersebut jarang diperhatikan oleh pengguna kitab. Oleh kerana itu penting untuk menjelaskan manhaj syarahan hadith yang terdapat dalam kitab ini agar dapat dikenali statusnya sekaligus untuk mengukur sejauh mana pengetahuannya dalam ilmu hadis. Kajian ini berhasrat mengeksplorasi manhaj syarahan hadis yang dilakukan Shaykh Nawawi al-Banteni dalam kitab Tanqih al-Qaul. Tujuan kajian ini adalah untuk menentukan dan menganalisis manhaj syarahan hadis yang digunakan oleh Shaykh Nawawi al-Banteni dan mengungkap sejauh mana pengetahuan dan statusnya sebagai sarjana hadith melalui kitab Tanqih al-Qaul. Metodologi kajian ini adalah kualitatif melalui kaedah kepustakaan dan reka bentuk analisis kandungan kitab Tanqih al-Qaul. Kajian ini mendapati bahawa secara umum manhaj yang digunakan oleh Shaykh Nawawi al-Banteni dalam mensyarah hadith adalah dengan menggunakan metode Ijmali. Dalam pengaplikasiannya beliau menggunakan teknik Interpretasi Tekstual melalui satu kaedah iaitu mensyarah hadith mengikut matan atau teks asal hadis, dan Interpretasi Intertekstual melalui satu kaedah juga yaitu mensyarahkan hadis dengan hadis. Kajian ini menemukan bahwa Shaykh Nawawi al-Banteni memiliki kemampuan dan pengetahuan yang baik dalam ilmu hadis. Selain itu dia juga dapat memberikan pemahaman kepada masyarakat tentang manhaj syarahan hadith yang dilakukan oleh Shaykh Nawawi al-Banteni dalam kitabnya Nasa’ih al-‘Ibad.]